DAMPAK ATURAN PEMBATASAN LOAN TO VALUE TERHADAP HARGA SAHAM PROPERTI - BANGUN G, JOSHUA Bangun (Jurnal Akuntansi AKUNESA, 2012)
The rule which is issued by the government more or less is always giving effect for the finance sectors generally and the stocks especialy. One of those rules is about Surat Edaran Bank Indonesia No. 14 / 10 / DPNP of Implementation of Risk Management in Banks Doing Lending for Home Ownership and Vehicle Credit. The purpose of the research is knowing the effect of that rule in properties and real estate stocks price activity. The description research through analyzing the stocks price activities graphic of the properties and real estate stocks. The author reach a conclusion that generally, stocks price is affected by the loan to value rule. Keywords: stocks, stocks price, properties and real estate, risk management in banks, , home ownership,loan to value.